2020
DOI: 10.1021/acs.biochem.9b01072
|View full text |Cite
|
Sign up to set email alerts
|

Revealing an Internal Stabilization Deficiency in the DNA Polymerase β K289M Cancer Variant through the Combined Use of Chemical Biology and X-ray Crystallography

Abstract: The human DNA polymerase (pol) β cancer variant K289M has altered polymerase activity in vitro, and the structure of wild-type pol β reveals that the K289 side chain contributes to a network of stabilizing interactions in a C-terminal region of the enzyme distal to the active site. Here, we probed the capacity of the K289M variant to tolerate strain introduced within the C-terminal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…At the same time, dissociation constants K d , polymerase reaction rate constant k obs , and rate of product release k ss are similar between the Polβ variant and wild type (WT) Polβ. The Lys289Met variant more frequently attaches dCTP opposite cytidine in DNA, thereby showing poor discrimination of dNTPs during the transferase reaction [25,26]. It has been demonstrated that the rate constant of dNTP incorporation into 1-nt gap-containing DNA in this variant is considerably lower than that of WT Polβ.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, dissociation constants K d , polymerase reaction rate constant k obs , and rate of product release k ss are similar between the Polβ variant and wild type (WT) Polβ. The Lys289Met variant more frequently attaches dCTP opposite cytidine in DNA, thereby showing poor discrimination of dNTPs during the transferase reaction [25,26]. It has been demonstrated that the rate constant of dNTP incorporation into 1-nt gap-containing DNA in this variant is considerably lower than that of WT Polβ.…”
Section: Introductionmentioning
confidence: 99%